Pilot study on the applicability and functionality of an ileostomy catheter: experience report (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To report a pilot study analyzing the applicability and functionality of an ileostomy catheter. Method: This is an experience report on the applicability and functionality of the catheter during insertion, in directing the effluent to a temporary collecting device, and in stabilization. Data were collected through systematic observation and video recording of one adult participant. Results: The innovative product, named the TomJeff® catheter, was inserted without difficulty; the effluent was directed to the temporary collecting device; and the catheter remained stable. The participant reported discomfort, pain, cramping, and fear from the period prior to insertion through removal; however, all symptoms were tolerated. Video recording allowed documentation of behaviors, expressions, and interactions, providing rich data and enabling review of all stages; however, it reduced spontaneity. Conclusion: The study enabled the identification of necessary adjustments to the catheter and validated its feasibility. Although it does not allow for generalizations, the results provide valuable support for the next steps of the research. The modifications made to the device, including resizing the catheter to facilitate insertion, demonstrate how technological development aligned with clinical practice can contribute to improving the user experience.